Racial and Ethnic Differences in the Association Between Classical Cardiovascular Risk Factors and Common Carotid Intima-Media Thickness: An Individual Participant Data Meta-Analysis - Engelbert A. Nonterah , MD, PhD; Nigel J. Crowther , PhD; Kerstin Klipstein-Grobusch , PhD; Abraham R. Oduro , MD, PhD; Maryam Kavousi , MD, PhD; Godfred Agongo , PhD; Todd J. Anderson, MD; Gershim Asiki , MD, PhD; Palwendé R. Boua , PhD; Solomon S. R. Choma , MSc; David J. Couper , PhD; Gunnar Engström , MD, PhD; et al. (My University, 2022)
BACKGROUND: The major risk factors for atherosclerotic cardiovascular disease differ by race or ethnicity but have largely been defined using populations of European ancestry. Despite the rising prevalence of cardiovascular disease in Africa there are few related data from African populations. Therefore, we compared the association of established cardiovascular risk factors with carotid-intima media thickness (CIMT), a subclinical marker of atherosclerosis, between African, African American, Asian, European, and Hispanic populations. METHODS AND RESULTS: Cross-sectional analyses of 34 025 men and women drawn from 15 cohorts in Africa, Asia, Europe, and North America were undertaken. Classical cardiovascular risk factors were assessed and CIMT measured using B-mode ultrasound. Ethnic differences in the association of established cardiovascular risk factors with CIMT were determined using a 1-stage individual participant data meta-analysis with beta coefficients expressed as a percentage using the White population as the reference group. CIMT adjusted for risk factors was the greatest among African American populations followed by Asian, European, and Hispanic populations with African populations having the lowest mean CIMT. In all racial or ethnic groups, men had higher CIMT levels compared with women. Age, sex, body mass index, and systolic blood pressure had a significant positive association with CIMT in all races and ethnicities at varying magnitudes. When compared with European populations, the association of age, sex, and systolic blood pressure with CIMT was weaker in all races and ethnicities. Smoking (beta coefficient, 0.39; 95% CI, 0.09–0.70), body mass index (beta coefficient, 0.05; 95% CI, 0.01–0.08) and glucose (beta coefficient, 0.13; 95% CI, 0.06–0.19) had the strongest positive association with CIMT in the Asian population when compared with all other racial and ethnic groups. High-density lipoprotein-cholesterol had significant protective effects in African American (beta coefficient, −0.31; 95% CI, −0.42 to −0.21) and African (beta coefficient, −0.26; 95% CI, −0.31 to −0.19) populations only. CONCLUSIONS: The strength of association between established cardiovascular risk factors and CIMT differed across the racial or ethnic groups and may be due to lifestyle risk factors and genetics. These differences have implications for race- ethnicityspecific primary prevention strategies and also give insights into the differential contribution of risk factors to the pathogenesis of cardiovascular disease. The greatest burden of subclinical atherosclerosis in African American individuals warrants further investigations.
Keywords: atherosclerosis ■ cardiovascular disease risk ■ carotid intima-media thickness ■ ethnicity ■ individual participant data meta-analysis ■ race